From Alt-text to Real Context: Revolutionizing image captioning using the potential of LLM - Vrajkumar Patel,; Aayush Modi,; Harsh Mistry,; Abhishesh Mishra,; Dr. Rocky Upadhyay,; Apoorva Shah, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The "From Alt-Text to Real Context" project harnesses the transformative capability of Meta Llama-3.2-11B-Vision-Instruct, thus unleashing an unprecedented image captioning system with advanced multimodal reasoning and attention mechanisms. These descriptions are richly contextual and domain-adaptive, moving them beyond the boundaries of traditional models. The platform has been constructed very carefully, keeping a heavy robust backend in Python (Flask/FastAPI) and an interactive frontend created in React.js for easier human interaction. With strong, advanced tools that include Hugging Face Transformers, OpenCV, NumPy, and Pandas, it shines for fine-tuning models, image preprocessing, and manipulation for particular, domain-specific customizations suited for a wide variety of applications from accessibility to e-commerce and education. The system generates alt-text and can perform complex image analysis and identify key features, providing more comprehensive scene descriptions. It is equipped with sentiment analysis to decipher emotive signals; it can provide critical metrics to quantify positive sentiment. This sophisticated AI system is built on the power of LLM outshines with zero-shot and multilingual capabilities and can also be utilized in tasks like image-based captioning and storytelling. Combining state-of-the-art AI, high adaptability, and great user-friendliness, this project raises new standards for contextual understanding, applicability in real-life scenarios, and image captioning.
Keywords: Meta Llama-3.2; Image captioning; Contextual descriptions; Hugging Face Transformers; Image analysis; Sentiment analysis; Zero-shot capabilities; Large Language Models